Influence of context on engagement with COVID-19 testing: a scoping review of barriers and facilitators to testing for healthcare workers, care homes and schools in the UK - Ben Lambert; Sassy Molyneux; Claire Marriott Keene; Prabin Dahal; Kasia Stepniewska; Sheetal Silal; Richard Lewis; Sabine Dittrich; Sunil Pokharel; Siyu Chen; Bo Gao; Umar Mahmood; et al. (BMJ Open)
Objective The UK government’s response to the COVID-19 pandemic included a ‘test, trace and isolate’ strategy. Testing services for healthcare workers, care homes and schools accounted for the greatest spend and volume of tests. We reviewed relevant literature to identify common and unique barriers and facilitators to engaging with each of these testing services.Design Scoping review.Search strategy PubMed, Scopus and the WHO COVID-19 Research Database were searched for evidence published between 1 January 2020 and 7 November 2022. This was supplemented by evidence identified via free-text searches on Google Scholar and provided by the UK Health Security Agency (UKHSA).Data extraction and synthesis Data were extracted by a team of reviewers and synthesised thematically under the broad headings of perceptions, experiences, barriers and facilitators to engaging with the COVID-19 testing programme.Results This study included 40 sources, including 17 from projects that informed UKHSA’s decisions during the pandemic. Eight themes emerged and were used to categorise barriers and facilitators to engaging with the testing services for healthcare workers, care homes and schools: (1) perceived value, (2) trust in the tests and public bodies, (3) importance of infrastructure, (4) impact of media and social networks, (5) physical burden of the test, (6) perceived capability to undertake testing, (7) importance of relevant information and 8) consequences of testing.Conclusions Universal barriers and facilitators to engagement with the testing programme related to the core elements of each testing service, such as uncomfortable specimen collection and the influence of media and peers; these could be mitigated or leveraged to increase engagement across settings. However, the individuals involved, perceptions of value and available resources differed across services, leading to unique experiences between settings. Thus, consideration of context is crucial when designing and implementing a testing programme in response to a pandemic.